Studies on 2-Substituted-6,8-dibromo-4(H)-3,1-benzoxazin-4-one - Mohammed, F.K.; Bakeer, H.M.; El-Hashash, M.A. (Asian Journal of Chemistry, 2010)
The behaviour of substituted 6,8-dibromo-4(H)-3,1-benzoxazin-4- one (II) towards nitrogen nucleophile (formamide, hydrazine hydrate, hydroxylamine, amines, o-phenylene diamine) to yield quinoazolinone (III-VII), respectively. When IV react with anhydrides, carbon electrophiles, aromatic ketone, benzylidine malononitrile, carbon disulphide, chloroacetyl chloride and ethylbromo acetate, benzoxazinone (II) to give quinazolinone (IX-XVIII). The reaction of III with ethylbromo acetate, methyl iodide and aromatic aldehyde were carried out to obtaine the quinazolinone derivatives (XIX, XXII, XXIII), respectively. The reaction of hydrazine hydrate on quinazolin-4-one (XIX) to form corresponding hydrazide XX which is converted to hydrazone XXI when reacted with aromatic aldehydes.